Publishing and Selling Jerónimo Nadal's Trend-Setting Evangelicae historiae imagines and Adnotationes et meditationes in evangelia: Dealings with the Moretuses, 1595–1645. (18th September 2019) - Bowen, Karen L; Imhof, Dirk
Abstract: This article examines how the Moretus family of printer-publishers in Antwerp quickly assumed control of the distribution of Nadal's famous Adnotationes et meditationes in evangelia and accompanying Imagines . The sale of both parts of this work is traced over more than fifty years. The ways in which the market for Nadal's publications burgeoned in the early seventeenth century and ultimately declined by the 1630s are documented. Essential throughout is the great diversity in the demand for these works. For amidst the exceptionally wide-spread, international interest in these works, there was a significant, as yet unrecognized demand for plain copies of the Adnotationes, without any accompanying illustrations. Hence, new insights are given for discussions of the actual spiritual and visual influence exerted by these remarkable publications in the decades immediately following their publication.